A randomized controlled trial of motivational interviewing as a tool to enhance secondary prevention strategies in cardiovascular disease (MICIS study). Issue 1 (4th March 2021) - Everett, B.; Salamonson, Y.; Koirala, B.; Zecchin, R.; Davidson, P.M.
Abstract : Background : Physical activity/exercise has consistently been shown to improve objective measures of functional capacity, enhance quality of life, improve coronary risk profile, and reduce mortality for individuals with coronary heart disease. Despite the gains achieved by those who attend cardiac rehabilitation (CR) many individuals fail to maintain lifestyle changes. Aim(s) : The aims of this study were to evaluate the effectiveness of motivational interviewing as a strategy for promoting maintenance of cardiac risk factor modification in patients who had participated in standard, 6-week outpatient CR programs. Methods : In a randomized controlled trail, participants in usual care and intervention group (Motivational interviewing supplemental to a standard 6-week CR program) were followed up at 6-weeks and 12-months. The primary outcome was distance walked on the six-minute walk test (6MWT), used as both an indicator of functional capacity and habitual physical activity. Secondary outcomes included modifiable coronary risk factors (smoking, self-reported physical activity, waist circumference, body mass index and medication adherence), psychological status (depression, anxiety, stress, perceived cardiac control, perceived social support, exercise self-efficacy) and quality of life. Results : Total 110 patients, usual care ( n = 58) and intervention ( n = 52), consented to participate in the study. Overall, demographic and clinical characteristics did not differ between groups at baseline. Motivational interviewing was no more likely to promote maintenance of cardiac risk factor modification (both primary and secondary outcomes) than a standard CR program alone. Both intervention and control groups maintained the gains achieved during CR at the 12-month follow-up except for weight loss. Conclusions : Although both groups maintained the gains achieved during CR for physical activity, there was no effect of the intervention on maintenance of cardiac risk factor modification on both primary and secondary outcomes.